THE ROLE OF EARLY MALADAPTIVE SCHEMAS ON ROMANTIC RELATIONSHIPS: A REVIEW STUDY - Eken, Ece (PEOPLE: International Journal of Social Sciences, 2017)
Human beings are a social entity, and the relationships have an important role in the lives of people. Beliefs and patterns of behavior in relationships are shaped by early life experiences (Bartholomew & Shaver, 1998; Hazan & Shaver, 1994). Ainsworth and Bowlby (1991) have stated that babies can only feel safe when they can have parent figures that care for them and take responsibility for the consequences of their behavior. A similar view of object relations and attachment theories is that the individual develops schemas according to the level of meeting the needs of early childhood and reflects these schemas to current life events (Rafaeli, Bernstein & Young, 2013). There are 18 early maladaptive schemas (EMSs) that arise due to most of the relational needs, and they arise in distressed relational processes. In the relationship, if the partners are faced with situations that trigger their schemas, they may be insufficient to meet each other's needs, show sensitivity and cognitive distortion (Young, Klosko & Weishaar, 2013). As a result, the purpose of this study is to briefly introduce the EMSs, to provide some research on the role of EMSs on romantic relationships, and to suggest recommendations to mental health professionals on how to conceptualize and treat romantic relationship problems. Research conducted over the past two decades shows that attachment problems persist in adulthood and these problems have a strong influence on a large number of behaviors in relationships. Research on the role of EMSs on romantic relationships show that schemas play an active role in adult-related conflict (Messman Moore and Coates (2007), divorce process (Yousefi, Etemadi, Bahrami, Ahmadi & Sadat Fatehi 2010), inclinations of romantic relationship (Cihan Güngör, 2015), marital satisfaction (Kebritchi, & Mohammadkhani, 2016), couple satisfaction and individual mate value (Dumitrescu, & Rusu, 2012). Thus, it can be said that moving through EMSs in relational problems enables the systematic understanding of emotional, cognitive and behavioral structures.